Transformation of the Meaning of Mawlid Nabi Celebration in the Praje Sasak Tradition - Syahputra, Muhammad Yusril Indra; Sulismadi; Sulistyowati , Tutik (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to explore the dynamics of the Prophet's birthday celebration and its impact on the identity and social cohesion of the local community. This study used a qualitative approach and ethnographic research type, data were collected through in-depth interviews and direct observation. Data analysis was conducted using an interactive method that includes data reduction, data presentation, and conclusion drawing or verification. The celebration of the Prophet's birthday in the Praje Sasak tradition in East Arong-Arong Village underwent a transformation due to modernization, including a shift from traditional music to modern music and the emergence of new entertainment elements. This transformation reflects a cultural convergence that enriches the identity of the Sasak people, but also poses challenges in maintaining traditional values. Through cultural education, community engagement and collaboration with outsiders, the original values of the Praje Sasak tradition can be preserved without losing its identity. The celebration of the Prophet Muhammad SAW is not only a spiritual moment, but also a reflection of the cultural identity of the Sasak people who continue to develop amid social and cultural dynamics.